2006
DOI: 10.1016/j.cub.2006.04.029
|View full text |Cite|
|
Sign up to set email alerts
|

High-Affinity Auxin Transport by the AUX1 Influx Carrier Protein

Abstract: In plants, auxin is a key regulator of development and is unique among plant hormones in that its function requires polarized transport between neighboring cells to form concentration gradients across various plant tissues. Although putative auxin-influx and -efflux transporters have been identified by using molecular genetic approaches, a detailed functional understanding for many of these transporters remains undetermined. Here we present the functional characterization of the auxin-influx carrier AUX1. Upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
209
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(224 citation statements)
references
References 34 publications
7
209
0
1
Order By: Relevance
“…3F). AUX1 importer recognizes the synthetic auxin 2,4-D and natural auxin IAA, but not NAA as a substrate (13,14). This substrate profile of AUX1 is consistent with the inhibitory profile of AUX1 by alkoxy-IAA and -NAA (6a-7b).…”
Section: Selected Alkoxy-auxin Analogs Inhibit Root Gravitropism Withsupporting
confidence: 57%
See 2 more Smart Citations
“…3F). AUX1 importer recognizes the synthetic auxin 2,4-D and natural auxin IAA, but not NAA as a substrate (13,14). This substrate profile of AUX1 is consistent with the inhibitory profile of AUX1 by alkoxy-IAA and -NAA (6a-7b).…”
Section: Selected Alkoxy-auxin Analogs Inhibit Root Gravitropism Withsupporting
confidence: 57%
“…The artificial auxin 2,4-D is incorporated into cells by the AUX1 importer and inhibits primary root growth. The auxin influx inhibitor 1-napthyloxy acetic acid restores 2,4-D-inhibited primary root growth by reducing the uptake of 2,4-D by the AUX1 importer (13,23). In an analogous experiment, Bz-IAA, but not Bz-NAA rescued 2,4-D inhibited root growth (supplemental Fig.…”
Section: Selected Alkoxy-auxin Analogs Inhibit Root Gravitropism Withmentioning
confidence: 73%
See 1 more Smart Citation
“…Third, auxin influx inhibitors, 1-NOA and CHPAA, phenocopy the root phenotype of aux1 [51]. Recently, experiments that included the heterologous expression of AUX1 in Xenopus oocytes directly demonstrated that AUX1 functions as a high-affinity, specific auxin uptake carrier [57]. AUX1 is expressed in various tissues, including protophloem cells, root columella cells, the lateral root cap and the shoot apical meristem [55,58].…”
Section: Aux1mentioning
confidence: 98%
“…It can also enter into cells by auxin importers of the amino acid permease families AUX1 (Auxin resistant 1), LAX (like-AUX1) and PGP4, a member of the MDR/PGP (Multidrug resistance/P-glycoprotein) families (Terasaka et al 2005;Yang et al 2006). This involves proton symport for AUX1 and ATP-driven uptake for PGPs (Fig.…”
Section: Auxin Import and Exportmentioning
confidence: 99%